UPAYA PENCEGAHAN DAN PENGENDALIAN DIABETES MELITUS BERDASARKAN DATA POSBINDU PTM DI PUSKESMAS TAHTUL YAMAN - Rini, Willia Novita Eka; Guspianto, Guspianto; Maharani, Andini Dwi (Jurnal Salam Sehat Masyarakat (JSSM), 2023)
Diabetes Mellitus is a metabolic disease characterized by high blood glucose levels (hyperglycemia) as a result of a deficiency of insulin secretion, impaired insulin activity or both. This Community Service (PKM) aims to carry out efforts to prevent and control Diabetes Mellitus in the Tahtul Yaman health center area. The activities carried out were counseling and outreach with the theme "Prevent and Control PTM" which was carried out at the Tahtul Yaman Health Center. Community education is provided in the form of exposure to material using digital media, namely power points, videos and print media in the form of posters and leaflets.